INSILICO STUDY AND DRUG TARGET FOR TYPE II DIABETES FROM A NATURAL COMPOUND - MARTHA LEEEMA ROSE; MURUGESH EASWARAN (International Journal of Pharma and Bio Sciences, 2012)
Diabetes is the most common disease in the world. Especially in India 90 to 95 % people have diabetes. People with type II diabetes tend to have two problems: they don't make quite enough insulin and the cells of their bodies don't seem to take in glucose as eagerly as they should. Anti-diabetic drugs treat diabetes mellitus by lowering glucose levels in the blood. But still no complete remedy performed to eradicate diabetes on the whole. Our present study focuses on inhibitory concept in cellular level can give drug target for typeII diabetes. It was realized that inhibition of all or some of the enzymes like α - amylase, α - glucosidase by inhibitors could regulate the absorption of carbohydrate and these inhibitors could be used therapeutically in the oral treatment of the non insulin dependent diabetes mellitus. Mangiferin is a xanthone isolated from roots of Salacia chinensis L. is a competitive inhibitor of α - glucosidase.